Spectral and temporal properties of RX J0520.5-6932 (LXP 8.04) during a type-I outburst - Vasilopoulos, G.; Haberl, F.; Sturm, R.; Maggi, P.; Udalski, A. (Astronomy and Astrophysics, 2014)
Aims: We observed RX J0520.5-6932 in the X-rays and studied the optical light curve of its counterpart to verify it as a Be/X-ray binary. Methods: We performed an XMM-Newton anticipated target-of-opportunity observation in January 2013 during an X-ray outburst of the source in order to search for pulsations and derive its spectral properties. We monitored the source with Swift to follow the evolution of the outburst and to look for further outbursts to verify the regular pattern seen in the optical light curve with a period of ~24.4 d. Results: The XMM-Newton EPIC light curves show coherent X-ray pulsations with a period of 8.035331(15) s (1σ). The X-ray spectrum can be modelled by an absorbed power law with photon index of ~0.8, an additional black-body component with temperature of ~0.25 keV, and an Fe K line. Phase-resolved X-ray spectroscopy reveals that the spectrum varies with pulse phase. We confirm the identification of the optical counterpart within the error circle of XMM-Newton at an angular distance of ~0.8'', which is an O9Ve star with known Hα emission. By analysing the combined data from three OGLE phases we derived an optical period of 24.43 d. Conclusions: The X-ray pulsations and long-term variability, as well as the properties of the optical counterpart, confirm that <ASTROBJ>RX J0520.5-6932</ASTROBJ> is a Be/X-ray binary pulsar in the Large Magellanic Cloud. Based on the X-ray monitoring of the source, we conclude that the event in January 2013 was a moderately bright type-I X-ray outburst, with a peak luminosity of 1.79 × 1036 erg s-1. Based on observations with XMM-Newton, an ESA Science Mission with instruments and contributions directly funded by ESA Member states and the USA (NASA); with Swift, a NASA mission with international participation.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; Be; Magellanic Clouds; pulsars: individual: RX J0520.5-6932; stars: emission-line; stars: neutron; X-rays: binaries